Distribution of Brazilian dermatologists according to geographic location, population and HDI of municipalities: an ecological study - Schmitt, Juliano Vilaverde [UNESP]; Miot, Hélio Amante [UNESP] (Sociedade Brasileira de Dermatologia, 2014)
This study investigated the geographic distribution of dermatologists in Brazilian municipalities in relation to the population, regions of the country and human development index. We conducted an ecological study based on data from the 2010 census, the 2010 human development index, and the records of the Brazilian Society of Dermatology. 5565 municipalities and 6718 dermatologists were surveyed. Only 504 (9.1%) municipalities had dermatologists, and accounted for 56.2% of the Brazilian population. The smallest population size and lowest HDI rate that best discriminated municipalities that did not have dermatologists were found to be 28,000 and 0.71, respectively. The average population density of dermatologists in cities was 1/23.000 inhabitants, and variations were independently associated with the HDI, the population of the municipalities and the region of the country.
Keywords: Dermatology; Human development; Social indicators